The de Sitter invariant special relativity: some physicals implications - Salcedo, Adriana Victoria Araujo [UNESP] (2017)
Due to the existence of an invariant length at the Planck scale, Einstein special relativity breaks down at that scale. A possible solution to this problem is arguably to replace the Poincare-invariant Einstein special relativity by a de Sitter invariant special relativity. Such replacement produces concomitant changes in all relativistic theories, including of course general relativity, which changes to what is called de Sitter modified general relativity, whose gravitational field equation is the de Sitter modified Einstein equation. A crucial property of this theory is that both the background de Sitter curvature and the gravitational dynamical curvature turns out to be included in the same curvature tensor. This means that the cosmological term Λ no longer explicitly appears in Einstein equation, and is consequently not restricted to be constant. In the first part of the thesis, a new definition for black hole entropy is defined. This new notion of entropy is strongly attached to the local symmetry, given the fact to be composed of two parts: the usual translational-related entropy plus an additional piece related to the proper conformal transformation. Also, it is obtained the de Sitter modified Schwarzschild solution, and using this solution we explore the consequences for the definition of entropy, as well as for the thermodynamics of the Schwarzschild-de Sitter system. In the second part the Newtonian limit of the de Sitter modified Einstein equation is obtained, and the ensuing Newtonian Friedmann equations are show to provide a good account of the dark energy content of the present-day universe. Finally, by using the same Newtonian limit, the circular velocity of stars around the galactic center is studied. It is shown that the de Sitter modified Newtonian force, which becomes effective only in the Keplerian region of the galaxy, could possibly explain the flat rotation curve of galaxies without necessity of supposing the existence of dark matter.